Cross border trade in grain between Nigeria and neighbouring Niger: Risk management assessment along Sokoto Illela-Konni border land - John Chiwuzulum Odozi (Cogent Economics & Finance, 2015)
Grain is an important marketable commodity that is hampered by risk of interrelated dimensions, particularly in borderlands of West Africa. Assessing the extent of risk in borderlands can be valuable for policy-makers and likely to contribute to increased regional trade through effective management. Risk management along the grain supply chain was investigated. The methodology was qualitative using desk review of literature and field survey and interviews. While the survey revealed evidence of substantial volume of grain exchange, most of the traders indicated transportation, high taxes and low production of grain as the most important risk factors limiting trade. Production was found to be limited by low access to agricultural insurance, fertilizer, irrigation and credit. Although farmers had access to production information, market information was inadequate. While public grain reserve exists to manage price risk; the capacity was insignificant compared to the magnitude of grain trade in the region. The guaranteed minimum grain price was not collectively determined but by government and their contractors.
Keywords: 330; regional trade; food security; risk; value chain; borderland; grain production